Pemberantasan Perdagangan Manusia: Tren, Hambatan, dan Hal Restitusi Korban - Tamala Yunfa, Shafiyyah (Taruna Law: Journal of Law and Syariah, 2024)
This paper discusses the issue of human trafficking that occurs in Indonesia. The development of human civilization changed the form of slavery to human trafficking. At first glance, it appears that the context of slavery in human trafficking occurs in the form of exploitation of human labor through disproportionate compensation. This is reinforced by Law no. 21 of 2007 concerning Eradication of the Crime of Human Trafficking. This paper aims to map trends, obstacles, and resistance rights of human trafficking victims. Normative juridical research method with a statutory approach. Recently, the trend of human trafficking in Indonesia is Indonesian Migrant Workers, commercial sex, child exploitation, and ship crew cases. The obstacle in eradicating this extraordinary crime is that there are many government officials and law enforcers who help smooth the actions of human traffickers so that the perpetrators are not subject to appropriate punishment. Seeing that law enforcement has not fully accommodated the rights of restitution for victims of human trafficking crimes has led to the emergence of victims' pessimistic views regarding the regulations in force in Indonesia.